Cubism in Pakistan: "An evolutionary glance" - Mughees, Shahnila * (Sunway University, 2014)
This paper reviews the cubist movement and its impact on the young artists in Pakistan. This practice-led research project investigates from an evolutionary perspective, how the Pakistani art scenario started to take a leap forward after the independence. Starting from Abdul Rahman Chughtai, Allah Bux and Sheikh Shujaullah’s conventional style, the modernism of Shakir Ali was soon found dominating the art scene. No wonder Shakir Ali is regarded as the first daring artist, responsible for introducing cubism into Pakistan. This study thus proves that it was cubism, which proved a vital source of art propagation and acted as a pillar for initiating new trends in the art genre of Pakistan. In conclusion, cubism also served as a platform for those artists who were striving to get new vistas for self-expression.